Influência da galactomanana das sementes do jucá na permeabilidade dentinária In vitro - Rabelo, Cibele Sales (2022)
Dentin hypersensitivity (DH) can be defined with sharp pain resulting from exposure of dentin to thermal, evaporative, tactile, osmotic or chemical stimulus. It is a condition that affects a large portion of the population. Therefore, it is necessary to develop therapies that are more effective in reducing DH. For this purpose, this study aimed to evaluate the influence of Caesalpinia ferrea (juca) seeds galactomannan at different concentrations in reducing dentinal permeability and tubular occlusion. It was in vitro and randomized study. Sixty 1 mm thick human dentin discs were used. The specimens were randomly divided into four experimental groups (n=12): distilled water (DW), potassium oxalate (PO), 1% juca seeds galactomannan (JSG1) and 2% juca seeds galactomannan (JSG2). To evaluate the durability of the treatments, all specimens were submitted to an erosive/abrasive cycle of 5 days. Dentin permeability was measured at three different times: after immersion in 17% ethylenediaminetetraacetic acid solution (EDTA) for 5 min, initial post-treatment, and post-cycling. Surface changes were evaluated initial post-treatment and post-cycling le by scanning electron microscopy (SEM). The data were submitted to the Kolmogorov-Smirnov test and, in view of the presence of normality, the ANOVA-2-way test for repeated measurements, was used followed by the Bonferroni post-test. The level of significance applied was 5%. For dentin permeability data, there was no significant difference between the groups at the initial post-treatment time (p>0.05). In the post-cycling period, JSG2 showed a reduction in permeability when compared to the DW (p<0.05). When the groups were compared at different times, only DW showed increased permeability (p<0.05). On the SEM images, the specimens treated with PO and JSG2 presented partially obliterated tubules, even after the erosive/abrasive cycle. The JSG was able to partially obliterate the dentinal tubules and maintain the dentin permeability in the face of abrasive and erosive challenges.